Polycystin-1 Assembles With Kv Channels to Govern Cardiomyocyte Repolarization and Contractility. Issue 11 (10th September 2019) - Altamirano, Francisco; Schiattarella, Gabriele G.; French, Kristin M.; Kim, Soo Young; Engelberger, Felipe; Kyrychenko, Sergii; Villalobos, Elisa; Tong, Dan; Schneider, Jay W.; Ramirez-Sarmiento, Cesar A.; Lavandero, Sergio; Gillette, Thomas G.; et al.
Abstract : Background: Polycystin-1 (PC1) is a transmembrane protein originally identified in autosomal dominant polycystic kidney disease where it regulates the calcium-permeant cation channel polycystin-2. Autosomal dominant polycystic kidney disease patients develop renal failure, hypertension, left ventricular hypertrophy, and diastolic dysfunction, among other cardiovascular disorders. These individuals harbor PC1 loss-of-function mutations in their cardiomyocytes, but the functional consequences are unknown. PC1 is ubiquitously expressed, and its experimental ablation in cardiomyocyte-specific knockout mice reduces contractile function. Here, we set out to determine the pathophysiological role of PC1 in cardiomyocytes. Methods: Wild-type and cardiomyocyte-specific PC1 knockout mice were analyzed by echocardiography. Excitation-contraction coupling was assessed in isolated cardiomyocytes and human embryonic stem cell-derived cardiomyocytes, and functional consequences were explored in heterologous expression systems. Protein-protein interactions were analyzed biochemically and by means of ab initio calculations. Results: PC1 ablation reduced action potential duration in cardiomyocytes, decreased Ca 2+ transients, and myocyte contractility. PC1-deficient cardiomyocytes manifested a reduction in sarcoendoplasmic reticulum Ca 2+ stores attributable to a reduced action potential duration and sarcoendoplasmic reticulum Ca 2+ ATPase (SERCA) activity. An increase in outward K + currents decreased action potential duration in cardiomyocytes lacking PC1. Overexpression of full-length PC1 in HEK293 cells significantly reduced the current density of heterologously expressed Kv4.3, Kv1.5 and Kv2.1 potassium channels. PC1 C terminus inhibited Kv4.3 currents to the same degree as full-length PC1. Additionally, PC1 coimmunoprecipitated with Kv4.3, and a modeled PC1 C-terminal structure suggested the existence of 2 docking sites for PC1 within the N terminus of Kv4.3, supporting a physical interaction. Finally, a naturally occurring human mutant PC1 R4228X manifested no suppressive effects on Kv4.3 channel activity. Conclusions: Our findings uncover a role for PC1 in regulating multiple Kv channels, governing membrane repolarization and alterations in SERCA activity that reduce cardiomyocyte contractility. Abstract : Supplemental Digital Content is available in the text.